Experiment Replication: A Proposed Solution for Developing Psychological Research in Indonesia - Muhammad Abdan Shadiqi; Hamdi Muluk; Mirra Noor Milla (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2019)
Is it possible that psychology can be a strong as natural science? Having replication studies could be the answer to this question. Philosophically, a replication is ‘the heart of any science,’ however it receives a little attention from social science. In Indonesia, there are three major problems: (1) only few number of researchers implement replication studies; (2) only few replication studies present strong evidence; and (3) only a small number of replication studies have been published. This might occur because the knowledge on how to conduct a replication study is inaccessible to most psychology researchers in Indonesia. This article explains a definition of a replication study, types of replications, and strategies to conduct replication experiments. I will explain how to conduct a replication study, starting from determining and reviewing reference articles to designing a replication study.